Empowering Cattle Farmers in Boyolali: Transforming Cow Manure into Sustainable Biofertilizer for Economic and Environmental Benefits - Wardhani, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Boyolali Regency, as the largest dairy cattle producer in Central Java, faces challenges in managing livestock waste, particularly cow manure. To address this, the Boyolali Regency Government, through the Environmental Agency (Dinas Lingkugngan Hidup/DLH), has constructed 600 biogas digesters to convert cow manure into biogas and digestate. However, the utilization of digestate as organic fertilizer has not been optimized. This study aims to enhance farmers' capacity to process digestate into biofertilizer through training, assistance, and demonstrations. Survey results indicate that most farmers have not utilized digestate effectively, leading to potential environmental pollution. Through the provided supports and assistances, farmers' knowledge of digestate processing significantly increased. The program also highlighted the potential of using digestate biofertilizer to reduce operational costs, increase farmers' income, and promote a sustainable agricultural and livestock system.